Study on the suitability of life cycle assessment for the estimation of donkey milk environmental impact - Andrea Bragaglio; Elio Romano; Maurizio Cutini; Eleonora Nannoni; Daniel Mota-Rojas; Salvatore Claps; Pasquale De Palo (Animal, 2024)
In the last decades, western Countries increased their interest in innovative products like donkey milk and other activities carried out with donkeys (onotherapy, onotourism). Donkey milk is considered a high-added-value food and is very similar to human breast milk. It is also used as an ingredient in cosmetics. The growing public interest suggests the need for a pilot study on the sustainability of donkey milk production, according to Life Cycle Assessment (LCA) criteria. Milk was used as the Declared Functional Unit (DFU) and two different models were described, a Real Scenario Model (RSM, i.e. a farm with its declared milk yield), and an Increased Milk Production Model (IMPM, i.e., the same farm with theoretically increased milk yield). Allocation was applied both in RSM and IMPM; thus, different values of impact categories, i.e., Global Warming Potential (GWP, kg CO2 equivalents), Acidification Potential (ACP, g SO2 equivalents) and Eutrophication Potential (EUP, g PO43−) were observed. GWP improved after mass allocation and showed the lowest equivalents in IMPM, compared to economic and reference allocation criterion (P < 0.05). In RSM, allocations affected GWP in a different way: the smaller size of the DFU resulted in the largest estimation of CO2 equivalents (P < 0.05) for reference allocation, whereas the mass allocation estimates were lower than with economic allocation (P < 0.05). ACP and EUP followed the same trends. No differences were found in IMPM results across the three allocation methods used. Moreover, mass allocation values recorded in RSM did not significantly differ from IMPM. ACP and EUP of RSM improved after economic allocation, although they were less sustainable (P < 0.05) than all IMPM values and RSM equivalents after mass allocation (P < 0.05). As expected, the theoretical model with increased milk yield improved the sustainability of the system. Both scenarios were affected by allocation criteria. In RSM, the economic and mass allocations described a representative scenario where donkey meat contributed to subtracting equivalents from milk (the main product). The present paper is a pilot study estimating for the first time the environmental impact of donkey milk production, with the aim to stimulate further research.